Quantifying posterior shoulder tightness in the athletic population - Kolber, M.; Hanney, W.; Benevento, J. D. (Strength and Conditioning Journal, 2012)
Posterior shoulder tightness (pst) has been implicated in the etiology of numerous shoulder disorders. Individuals participating in overhead sports and weight training have a predilection for pst, thus a measurement designed to identify pst may offer considerable prescriptive utility. This column presents 2 valid and reliable methods for quantifying pst.